Handedness and the control of human technology and language - Gregory Kroliczak; Lukasz Przybylski (Humanities & Social Sciences Communications)
Abstract The impact of handedness on neural substrates of common tool processing and tool use skills as proxies to the mechanisms underlying modern reciprocal relationships among humans and their brains, the tools they create and use, and technologies they implement and utilise, has only recently started to be elucidated. Yet, as most of the reports on lateralisation of such processing or skills focused on a single task, and sharp divisions of participants into right-, left-, and mixed-handed, or non-righthanded for the latter two groups combined, little is known about interrelationships between the neuronal underpinnings of different skilled manual actions—e.g., manual praxis skills in the form of disparate hand-tool interactions, including their most common neural phenotypes in the population at large. Here, in 62 individuals with different handedness status, we studied the laterality of two praxic abilities involving common tools. Even though their neural substrates were expected to be closely linked, we identified numerous cases (in 7/28 righthanders [RH] – 25%, and in 6/21 lefthanders [LH] – 29% of participants) with hemispheric dissociations in the underlying mechanisms. They involved both right-lateralised functional grasp planning vs. left-lateralised visual tool use (8% of all tested cases, 3/28 RH: ~11%, and 2/21 LH: ~10%), and vice versa (13% of all cases, 4/28 RH: ~14%, and 4/21 LH: ~19% of participants). The laterality/organisation of these praxic skills was also compared to the laterality/organisation of productive language, with only few cases of dissociations identified. The observed phenotypes are discussed in the context of coevolutionary hypotheses linking ancient toolmaking and tool use skills, the associated cultural evolution, technological innovations, and language to the cortical expansion and functional lateralisation in human evolution.